MAGMARS: A Melting Model for the Martian Mantle and FeO‐Rich Peridotite. Issue 12 (14th December 2021) - Collinet, Max; Plesa, Ana‐Catalina; Grove, Timothy L.; Schwinger, Sabrina; Ruedas, Thomas; Breuer, Doris
Abstract: Martian basalts identified by rover in‐situ analyses and the study of meteorites represent a direct link to the melting process in the planet's interior and can be used to reconstruct the composition of the mantle and estimate its temperature. Experimentally calibrated numerical models are powerful tools to systematically search for the mantle compositions and melting conditions that can produce melts similar to primary basalts. However, currently available models are not suitable for modeling the melting of FeO‐rich peridotites. In this study, we present experiments performed at 1.0 and 2.4–2.6 GPa on a primitive Martian mantle with various P2 O5 contents. We use the new experiments together with a comprehensive database of previous melting experiments to calibrate a new model called MAGMARS. This model can reproduce the experimental melt compositions more accurately than Gibbs free energy minimization software (e.g., pMELTS) and can simulate near‐fractional polybaric melting of various mantle sources. In addition, we provide an updated thermobarometer that can estimate the P – T melting conditions of primary melts and can be used as a prior step to constrain the input parameters of the MAGMARS melting model. We apply MAGMARS to estimate the source composition of the Adirondack‐class basalts and find that melting a depleted mantle, at 2.3–1.7 GPa ( T p  = 1390 ± 40°C) can best explain their bulk composition and K2 O/Na2 O ratio. MAGMARS represents a fast and accurate alternative to calculate the composition of the Martian primary melts and can be used as a stand‐alone package or integrated with geodynamical models or other independent modeling software. Plain Language Summary: Martian rocks that have been analyzed by rovers can be used to reconstruct the interior of Mars through time. These samples reflect the conditions (temperature, pressure, and chemistry) that have been present in the interior at the time of their formation. Using laboratory experiments, computer models can be built to reproduce the formation of such rocks on Mars. However, large discrepancies between models and laboratory experiments have been observed, in particular for iron‐rich compositions, which makes it difficult to validate the models and leads to large uncertainties. Here we combine experiments with a new model that can accurately reproduce the chemistry of Martian rocks. This model has the ability to constrain the temperature, pressure, and chemical composition of the interior that match the composition observed at the surface of Mars. We apply this model to estimate the melting conditions of Adirondack‐class basalts and find that these can be reproduced by a depleted mantle and lower temperature as previously suggested. This model has the advantage of being computationally fast and can be combined with geodynamical models or other independent models in the future. Key Points: We performed melting experiments and reversal experiments to constrain the composition of Martian primary melts MAGMARS is a new model simulating the near‐fractional polybaric melting of FeO‐rich mantle compositions The Adirondack basalts can be produced by polybaric melting of a depleted mantle with a mantle T p  = 1390 ± 40°C